ANALISIS PARETO 80/20 UNTUK PENGENDALIAN BIAYA PEKERJAAN ARSITEKTUR HOTEL BERTINGKAT TINGGI - Nadiifa Firsty; Yani Rahmawati (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: Hotel construction projects are highly complex, involving numerous categories of architectural work that make it difficult to prioritize the budget. Without a systematic approach, project managers risk allocating resources to items with little impact. This study applies the Pareto 80/20 principle to analyze the distribution of architectural work costs in the construction of the Voyou Bengawan Surakarta Hotel, a 14-story hotel on Jalan Ir. Sutami, Surakarta City, Central Java. The primary data is sourced from the Bill of Quantities (BoQ) for all architectural work from the basement to the 14th floor, with a total value of Rp23,413,906,489 divided into seven categories. The method used is descriptive quantitative analysis involving Pareto ranking, percentage calculations, and cumulative analysis using Microsoft Excel. The results identify four categories as the